(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the diagnostic accuracy of ultrasonography following ovarian neoplasms referred for laparotomy. Study Design: It was a single-center study Place and Duration of Study: This study was conducted at the Department of Radiology, HMC Peshawar, Pakistan from January 2023 to July 2023. Methods: Women aged between 25-65 presented with an ovarian lesion of more than 9 cm size on ultrasonography. Laparotomies were performed subsequently, and the histological findings were considered the gold standard. Proceeded to laboratory correlation using 02 x 02 tables inclusive of sensitivity, specificity, positive predictive value , and negative predictive value , and overall diagnostic accuracy with histology as the gold standard. Results: Out of the 100 subjects, an average of 33.02 ± 04.37 years was the mean age, and the average duration of symptoms was 26.66 ± 12.01 months. 87 subjects (87.8%) presented with more than two parities, while thirteen of them (12.8%) had only one. The sensitivity of ultrasonography was 80.62%, specificity was 75.70%, PPV was 95.88%, NPV was 51.62%, and the overall diagnostic accuracy was 71.21% for differential diagnosis of malignancy following ovarian neoplasms with histology as the gold standard. Conclusion: Compared to histology, ultrasonography shows a high level of sensitivity and diagnostic accuracy while demonstrating moderate specificity in detecting malignant ovarian neoplasms. Conclusion: The study proved the efficacy of ultrasonography in the examination of ovarian neoplasms, showing high sensitivity and PPV. Although specificity and NPV were fair, ultrasonography proved to be the noninvasive imaging technique. Future research should focus on challenges related to the identification of sophisticated lesions to enhance diagnostic test accuracy and patient outcomes.